Supplementation of Sauropus androgynus (L.) Merr leaves extract reduced more body weight and triglyceride in obese male wistar rats with moderate exercise - Christine Icasia; Alex Pangkahila; I Wayan Weta (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: Moderate exercise is one of the pillars of weight management. Supplementation of ingredients containing bioactive compounds such as Sauropus androgynus (L.) Merr leaves extract which contains flavonoids, tannins, and saponins may help obesity management. The purpose of this study was to prove that supplementation of Sauropus androgynus (L.) Merr leaves extract reduced more body weight and triglyceride in obese male Wistar rats with moderate exercise. Methods: This research was an experimental study with a randomized pretest-posttest control group design. The subjects were 20 rats (Rattus norvegicus). Obesity and hypertriglyceridemia were induced by a high-fat and high-carbohydrate diet. Rats were divided into two groups, namely the control group and the treatment group. Results: The control group there was a decrease in body weight (from 284.5±3.17 to 278.3±4.27 grams; p <0.001) and a decrease in triglyceride levels (from 186.7±14.8 to 181.1±13.6; p = 0.047). In the treatment group there was also a decrease in body weight (from 282.1±5.72 to 272.2±3.55 grams; p <0.001) and a decrease in triglyceride levels (from 185.4±9.24 to 160.2±22.5; p = 0.003). The decrease in body weight in the treatment group was more than in control group (-9.90±3.37 vs -6.20±2.74; p = 0.018). Triglyceride levels in treatment group also decreased more than in control group (-25.2±19.3 vs -5.60±8.13; p = 0.008). Conclusion: Based on the results of this study, it can be concluded that supplementation of Sauropus androgynus (L.) Merr leaves extract reduced more body weight and triglyceride in obese male Wistar rats with moderate exercise.